2020
DOI: 10.1177/0306624x20928025
|View full text |Cite
|
Sign up to set email alerts
|

Finding Colour in Conformity Part II—Reflections on Structured Professional Judgement and Cross-Cultural Risk Assessment

Abstract: There has been an increasing interest in cross-cultural risk assessment over the past 5 years. Much of this has been driven by concerns that particular risk instruments may be biased against, or ill-suited to, non-White offending populations. A growing body of work has asserted that unique cultural-specific risk factors and experiences may not be adequately considered within current risk assessment frameworks which have led to calls to culturally alter/remodel risk instruments. While recognising the importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…If a forensic risk tool is culturally augmented, then predictive accuracy for relevant outcomes needs to be consistent with established, orthodox risk instruments; clients and agencies would be at a disservice if predictive validity was sacrificed for face validity. Shepherd and Spivak (2021) further caution that the inclusion of ethnoculturally specific variables that are unique to a group and their circumstances (e.g., cultural erosion, experiences of racism), runs the risk of (a) criminalizing such experiences as they become a variable that is now a marker of elevated recidivism risk and (b) potentially inflating the risk levels of individuals from that ethnocultural group since given that they more than likely possess the experience or characteristic.…”
Section: Resultsmentioning
confidence: 99%
“…If a forensic risk tool is culturally augmented, then predictive accuracy for relevant outcomes needs to be consistent with established, orthodox risk instruments; clients and agencies would be at a disservice if predictive validity was sacrificed for face validity. Shepherd and Spivak (2021) further caution that the inclusion of ethnoculturally specific variables that are unique to a group and their circumstances (e.g., cultural erosion, experiences of racism), runs the risk of (a) criminalizing such experiences as they become a variable that is now a marker of elevated recidivism risk and (b) potentially inflating the risk levels of individuals from that ethnocultural group since given that they more than likely possess the experience or characteristic.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, one practical implication of these findings may be focused on identifying the risk factors that contribute less to mean score differences (substance abuse and personality/behavior in this study), and weighting them more heavily in risk assessment than the rest of the risk factors (Skeem & Lowenkamp, 2016). However, other researchers note that efforts to culturally amend instruments (such as including new items or weighting them differently) could paradoxically reduce accuracy and increase bias (Shepherd & Spivak, 2020). That is, these modifications may lower the predictive validity for this specific group, or on the contrary may increase it while decreasing the accuracy for subgroups within this cultural group (e.g., Roma females).…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of policies that focus on dynamic risk and needs rather than static items will more accurately adhere to evidence-based practices that reduce recidivism. It is crucial that modifications to risk assessment instruments be made based on evidence (Shepherd & Spivak, 2021). To this end, research has already indicated that dynamic risk factors are promising predictors of recidivism (Clarke et al, 2017; Lloyd et al, 2020; Perrault et al, 2017; Ward & Fortune, 2016; Yukhnenko et al, 2019); the current study adds to this growing body of evidence.…”
Section: Discussionmentioning
confidence: 99%